Comparing maritime piracy along the coasts of Africa: In search of a solution for the Gulf of Guinea. (2nd July 2020) - Barla, Christina; Agarwala, Nitin
ABSTRACT: Merchant ships at sea have been under threat for centuries from criminal activities such as maritime piracy and armed robbery. Such acts have seen a rise in recent years, with new breeding grounds mushrooming across the globe. In Africa, such criminal activities are as old as maritime trade, with three severely affected regions, each with its own dynamics. While piracy on the eastern coast (Gulf of Aden) has been brought under control by international maritime forces and that on the south-eastern coast (Mozambique Channel) by local maritime forces, piracy on the western side (Gulf of Guinea) continues unabated and has become a matter of concern for the world's maritime fraternity. In an effort to find a solution for piracy in the Gulf of Guinea, this article aims to compare and analyse incidents of piracy along the coasts of Africa and understand whether the countermeasures adopted on the eastern coasts can be replicated on the western one.